2006
DOI: 10.1103/physrevb.74.195201
|View full text |Cite
|
Sign up to set email alerts
|

Different temperature and pressure behavior of band edge and N-cluster emissions inGaAs0.973Sb0.022N0.005

Abstract: The photoluminescence of GaAs 0.973 Sb 0.022 N 0.005 was investigated at different temperatures, pressures, and excitation powers. Both the alloy band edge and the N-cluster emissions, which show different temperature and excitation power dependences, were observed. The pressure coefficients obtained in the pressure range of 0 -1.4 GPa for the band edge and N-related emissions are 67 and 45 meV/ GPa, respectively. The N-cluster emissions shift to higher energy in the lower pressure range and then begin to reds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(45 citation statements)
references
References 31 publications
1
44
0
Order By: Relevance
“…First, we sketch the case when strength of interaction between segments takes a constant value. Transport is induced by the constant thermal bias between reservoirs, that in the absence of time-dependent perturbations the dc heat current is given by the well-known Landauer-Büttiker formula for phononic systems [24,26]:…”
Section: Resultsmentioning
confidence: 99%
“…First, we sketch the case when strength of interaction between segments takes a constant value. Transport is induced by the constant thermal bias between reservoirs, that in the absence of time-dependent perturbations the dc heat current is given by the well-known Landauer-Büttiker formula for phononic systems [24,26]:…”
Section: Resultsmentioning
confidence: 99%
“…Under this condition, if the pressure goes on increasing, the X CBM of GaAs will be lower than the Γ CBM of GaAs and the band gap of GaAs will change from the direct band to the indirect band gap. It is reported that the pressure which the crossover between the X CBM of GaAs and the Γ CBM of GaAs corresponds to is 3.9 GPa to 4.2 GPa [12][13][14][15]. For GaN x As 1−x , it is found that when the pressure does not exceed 12 GPa, GaN x As 1−x still has a direct band gap, which shows that GaN x As 1−x needs much larger pressure than GaAs to realize the transition from the direct band gap to the indirect band gap.…”
Section: Physical Model and Discussionmentioning
confidence: 99%
“…Then, in GULP, the force constant Kc can be given by the second derivatives with respect to the potential energy. As is calculated, the phonon thermal conductance can be given by ∞ , 43 where is the Bose-Einstein distribution function.…”
Section: ιι Model and Methodsmentioning
confidence: 99%